Comparison between Optical COherence tomography guidance and Angiography guidance in percutaneous coronary intervention (COCOA): Study protocol for a randomized controlled trial. Issue 2 (August 2018) - Kubo, Takashi; Shinke, Toshiro; Okamura, Takayuki; Hibi, Kiyoshi; Nakazawa, Gaku; Morino, Yoshihiro; Shite, Junya; Ino, Yasushi; Kitabata, Hironori; Shimokawa, Toshio; Akasaka, Takashi
Highlights: COCOA is a randomized study comparing OCT-guided PCI vs. angiography-guided PCI. COCOA hypothesized that OCT-guided PCI would achieve greater stent area. When completed, COCOA will exert an influence on the pivotal PCI guidelines. Abstract: Background: Optical coherence tomography (OCT) is increasingly used as an adjunct to coronary angiography for guiding percutaneous coronary intervention (PCI). The current consensus on PCI is that the large final stent area offers the best chance of a good late clinical outcome. Since OCT provides more accurate information about the coronary artery and implanted stents, OCT-guided stent implantation is expected to achieve greater stent expansion than angiography guidance alone. Therefore, we designed the COCOA (Comparison between Optical COherence tomography guidance and Angiography guidance in percutaneous coronary intervention) study to evaluate whether OCT-guided stent implantation would result in a minimum stent area greater than that achieved with angiography guidance alone. Methods and design: The COCOA study is a large-scale, multicenter, single country (Japan), prospective randomized controlled, open-label, parallel group, superiority study comparing OCT-guided PCI with angiography-guided PCI. The eligible patients ( n = 550) are randomly allocated in a 1:1 ratio to receive either OCT-guided PCI or angiography-guided PCI. PCI is performed using the everolimus-eluting stent in accordance with certain criteria of OCT or angiography for optimal stent implantation. Following the stent optimization guided by OCT or angiography alone, OCT is performed in both groups. The primary endpoint is minimum stent area at post-PCI with allocated imaging guidance. Conclusion: When completed, the COCOA study will contribute to define the clinical value of the OCT guidance in PCI.